A rover's geologic field campaign: Exploration of the Kimberley by Curiosity. Issue 3 (11th March 2017) - Minitti, Michelle E.
Abstract: The Mars Science Laboratory Curiosity rover undertook comprehensive exploration of the Kimberley waypoint within Gale crater, Mars in order to understand its context within the larger geologic picture of Gale crater and its evidence for past Martian habitability. Coordinated observations from Curiosity's rich science payload revealed important insights into new Martian crustal compositions, the prevalence and diversity of sedimentary processes within Gale crater, and surface erosion rates. Exploration at the Kimberley, in part informed by a decade of orbital observations of Gale crater, underscored the critical synergy between landed and orbital observations and furthered understanding of complex geological processes on Mars. Key Points: The Mars Science Laboratory Curiosity rover carried out a comprehensive field campaign at the Kimberley waypoint, Gale crater, Mars Observations at the Kimberley revealed insights into new crustal compositions sedimentary processes, and surface erosion rates Synergistic orbital and landed observations improve understanding of complex geologic processes and refine rover exploration activities